Health education and community mobilization in Nigeria;issues and prospects - O., Ogbonna Brian; N., Ezenekwe Lizette; P., Isidienu Chika (International Journal Of Community Medicine And Public Health, 2017)
The importance of health to national development and poverty reduction over the centuries, in that improving health status and increasing life expectancy contribute to long-term economic development. This article examined the state of health education and community mobilization in Nigeria’s health care delivery. The electronic search of relevant materials was carried out and those that met the inclusion criteria were used for the study. Health literacy is vital to power and support government efforts in promoting health for all. Study suggested that 80% of Africans use traditional medicines while 85% of Nigerians consult traditional medicine healers. Many developing countries, especially those in Sub-Saharan Africa, in the 1970s experienced remarkable and unacceptable inequalities in the provision and distribution of health services. This contributed to and explained the exploration of different approaches to improve health care delivery by international health organizations in the 1970s.